The Need for Involving Third Parties in Dealing with ASEAN’s Marine Debris Problem - Idris Idris; Achmad Gusman Catur Siswandi; Arfin Sudirman; Amanda Yola Elvarina Sipahutar; Mursal Maulana (Balobe Law Journal, 2022)
Introduction: Marine debris has been a major problem towards ASEAN environment for the past decade, with several of its member state becoming the largest sources of marine derbis globally. The article presents three main causes of marine debris and reviewing how and to what extend ASEAN has attempted to stop or prevent the continuation of these causes.Purposes of the Research: This study aims to see whether main causes of ASEAN Marine Debris has already been tackled by ASEAN frameworks and policies, while also taking a third-party recommendation for consideration.Methods of the Research: This research was contucted using a normative juridical approach by examining literature studies or secondary data related to the research objects.Results of the Research: The result of this paper is that there is still a gap between the main causes of marine debris in ASEAN and the solution and steps planned out within ASEAN frameworks, which need to be filled with further research and study, conducted by ASEAN with collaboration from third parties.